Autologous dendritic cell-based immunotherapy (DCVAC/LuCa) and carboplatin/paclitaxel in advanced non-small cell lung cancer: A randomized, open-label, phase I/II trial. (2021) - Zemanova, Milada; Cernovska, Marketa; Havel, Libor; Bartek, Tomas; Lukesova, Sarka; Jakesova, Jitka; Vanasek, Jaroslav; Reiterer, Pavel; Kultan, Juraj; Andrasina, Igor; Siskova, Lenka; Koubkova, Leona; et al.
Highlights: Dendritic cell-based immunotherapy (DCVAC/LuCa) plus a platinum doublet in NSCLC. SLU01: a multicenter, open-label, parallel-group, randomized, phase I/II trial. DCVAC/LuCa improved OS and PFS in patients with stage IV NSCLC. DCVAC/LuCa in combination with carboplatin and paclitaxel was well tolerated. Abstract: Purpose: To investigate the efficacy and safety of an active cellular immunotherapy (DCVAC/LuCa) and chemotherapy in patients with stage IV non-small cell lung cancer (NSCLC). Patients and Methods: SLU01 was a multicenter, open-label, parallel-group, randomized, phase I/II trial. NSCLC patients were randomized in a ratio of 1:1:1 to receive: DCVAC/LuCa and chemotherapy (carboplatin and paclitaxel; Group A); DCVAC/LuCa, chemotherapy, pegylated interferon- α 2b, and hydroxychloroquine (Group B); or chemotherapy alone (Group C). DCVAC/LuCa was administered subcutaneously every 3–6 weeks (up to 15 doses). The primary endpoint was overall survival (OS). During the study, enrollment into Group B was discontinued for strategic reasons. Results: Forty-five patients were randomized to Group A, 29 patients to Group B, and 38 patients to Group C. The median OS in the modified intention-to-treat (mITT) population was 3.7 months longer in Group A than in Group C (15.5 vs. 11.8 months; p = 0.0179; hazard ratio = 0.54; 95% confidence interval: 0.32–0.91). This OS effect was consistent across subgroups of the mITT population (females, males, current smokers, former smokers, and patients with non-squamous and squamous cell histology). The most common treatment-emergent adverse events of any grade reported in Groups A, B, and C, respectively, were neutropenia (50.0%, 29.6%, and 20.6%), fatigue (40.0%, 18.5%, and 20.6%), anemia (35.0%, 44.4%, and 32.4%), paresthesia (27.5%, 25.9%, and 17.6%), and alopecia (25.0%, 29.6%, and 41.2%). Conclusion: DCVAC/LuCa in combination with carboplatin and paclitaxel extended OS and was well tolerated.